Beauveria bassiana affects immature stage development of Prostephanus truncatus (Coleoptera: bostrichidae) in stored maize. Issue 11 (1st November 2016) - Acheampong, Mavis A.; Cornelius, Eric W.; Eziah, Vincent Y.; Fening, Ken O.; Luke, Belinda; Moore, Dave; Clottey, Victor A.; Storm, Clare; Potin, Olivier
ABSTRACT: Recent research in Ghana has demonstrated the effectiveness of an isolate of B. bassiana, sensu lato (IMI 389521) from the U.K. against the larger grain borer Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae), a major pest of stored maize. To determine whether this isolate is effective on immature stages of P. truncatus, a laboratory study of the response of immature stages (egg, larvae and pupae) of P. truncatus in maize grains to two concentrations (1 × 10 9 and 3.16 × 10 9 cfu/kg maize) of B. bassiana, IMI 389521 formulated with Entostat™ and kaolinite was undertaken. Adult emergence, per cent survival of adults that emerged and the number of larvae in each immature stage were assessed after 45 days. Apart from the egg experiment, higher numbers of adults emerged in grains containing larvae and pupae treated with B . bassiana product compared to the untreated maize control. This notwithstanding, survival of emerged adults of P . truncatus was greatly reduced in B. bassiana treatments (<10%) compared with 75–95% in the controls. Surface treatment with B. bassiana on pre-infested maize showed a significant effect on the developmental biology of P. truncatus in Ghana.